Eight new species of Arge from South Africa and Namibia (Hymenoptera: Symphyta: Argidae) - Koch, F.; Goergen, Georg E. (2010)
As preamble to the preparation of a field guide to the sawflies (Symphyta) of Namibia and the westem part of South Africa eight species of Arge Schrank 1802 are presently newly described: Arge cochraneae sp. nov., A. elandsbayensis sp. nov., A. hereroensis sp. nov., A. krabbefonteinensis sp. nov., A. langebergensis sp. nov., A. montana sp. nov., A. namaensis sp. nov. and A. whiteheadi sp. nov. The genitalia of the new species are illustrated and their taxonomic relationships discussed. Maps showing their current known distribution are included.